PENGARUH PELATIHAN TERHADAP PENINGKATAN KREATIVITAS MELALUI PENINGKATAN KOMPETENSI TENAGA PENDIDIK DENGAN BERBASIS TEKNOLOGI STEAM (Studi Pada Peserta Pelatihan Tahun 2021-2022 Kabupaten Ciamis) - Dzikri, Fikri Fauzan (Journal of Management Review, 2025)
The study is backed up because of a delay in problems that are successfully identified as follows. The faculty cannot create innovations in learning. The faculty can't collaborate on something that can create something interesting in learning. It cannot create a pleasant learning atmosphere. Low use of the learning media in the teaching process. In this case, according to the interview with the Ciamis district head of education, the study still uses a simple approach. So it does not enhance students' enthusiasm for learning. Thus the purpose of this study is to know the impact of training on increased creativity educators through increased competence with high-technology based steam in Ciamis participants of the 2021-2022 district training program. The methods used are descriptive and verifiable research methods. Research shows that training has a positive and significant impact on the increased creativity of educators with steam technology-based students in Ciamis district 2021-2022, meaning that if training is carried out continually, the increased creativity of the educator will be increased. Increased competence has a positive and significant impact on the increased creativity of more educators with steam technology-based coaching in Ciamis district 2021-2022, meaning that if competence is carried out continually, the increased creativity of more educators will be increased. Training has a positive and significant impact on the increased creativity of more educators through increased competence with high-technology based steam in Ciamis residents of 2021-2022 district training. It means that if the training is carried out with increased competence, then the creativity of the educator will be increased.